Foldl as foldr alternative: Difference between revisions
No edit summary |
No edit summary |
||
Line 84: | Line 84: | ||
where | where | ||
whosit x r = \a -> r (f a x) | whosit x r = \a -> r (f a x) | ||
</haskell | </haskell> | ||
The way to look at this final expression is that <hask>whosit</hask> takes an element of the list, a function produced by folding <hask>f</hask> into the rest of the list, and the initial value, <hask>a</hask> of an accumulator. It applies <hask>f</hask> to the accumulator it's given and the list element, and passes the result forward to the function it got. | The way to look at this final expression is that <hask>whosit</hask> takes an element of the list, a function produced by folding <hask>f</hask> into the rest of the list, and the initial value, <hask>a</hask> of an accumulator. It applies <hask>f</hask> to the accumulator it's given and the list element, and passes the result forward to the function it got. |
Revision as of 05:02, 4 September 2014
This page explains how foldl
can be written using foldr
. Yes, there is already such a page! This one explains it differently.
The usual definition of foldl
looks like this:
foldl :: (a -> x -> r) -> a -> [x] -> r
foldl f a [] = a
foldl f a (x : xs) = foldl f (f a x) xs
Now the f
never changes in the recursion, so we don't really have to worry too much about it. For simplicity, then, let's pick one in particular:
f :: Ord x => Set x -> x -> Set x
f a x = insert x a
While we're at it, let's give a name to foldl f
: stuff
. So
stuff :: Ord x => Set x -> [x] -> Set x
stuff a [] = a
stuff a (x:xs) = stuff (f a x) xs
takes all the elements of the list it's given and stuffs them into the Set
it's given.
For some reason (maybe we're crazy; maybe we want to do weird things with fusion; who knows?) we want to write this using foldr
. Haskell programmers like curry, so it's natural to see stuff a xs
as (stuff a) xs
—that is, to see stuff a
as a function that takes a list and returns the result of folding f
into the list starting with an accumulator value of a
. This perspective, however, is the wrong one for what we're trying to do here. So let's change the order of the arguments of stuff
.
stuffy :: Ord x => [x] -> Set x -> Set x
stuffy [] a = a
stuffy (x : xs) a = stuffy xs (f a x)
So now we see that stuffy xs
is a function that takes an accumulator and uses it as the initial value to fold f
into xs
. With this shift of perspective, we can rewrite stuffy
just a little:
stuffy :: Ord x => [x] -> Set x -> Set x
stuffy a [] = \a -> a
stuffy (x : xs) = \a -> stuffy xs (f a x)
Believe it or not, we're almost done! How is that? Let's parenthesize a bit for emphasis:
stuffy :: Ord x => [x] -> Set x -> Set x
stuffy [] = (\a -> a)
stuffy (x : xs) = \a -> (stuffy xs) (f a x)
This isn't an academic paper, so we won't mention Graham Hutton's "Tuturial on the Universality and Expressiveness of Fold", but stuffy
fits the foldr
pattern:
stuffy :: Ord x => [x] -> Set x -> Set x
stuffy ys = foldr whatsit (\a -> a) ys
where
whatsit x r = \a -> r (f a x)
Substituting this in,
stuffy :: Ord x => [x] -> Set x -> Set x
stuffy list a = (foldr whatsit (\a -> a) list) a
where
whatsit x r = \a -> r (f a x)
And that's just about it! We wanted stuff
, however, not stuffy
, so let's swap the argument order again:
stuff :: Ord x => Set a -> [x] -> Set x
stuff a list = (foldr whatsit (\a -> a) list) a
where
whatsit x r = \a -> r (f a x)
Now since we do want to be able to use general foldl
forms, we should gneralize it again:
foldl :: (a -> x -> r) -> a -> [x] -> r
foldl f a xs = (foldr whosit (\a -> a) list) a
where
whosit x r = \a -> r (f a x)
The way to look at this final expression is that whosit
takes an element of the list, a function produced by folding f
into the rest of the list, and the initial value, a
of an accumulator. It applies f
to the accumulator it's given and the list element, and passes the result forward to the function it got.